Effect of Epoxy Resin and Fiberglass Addition on the Compressive and Splitting Tensile Strength of Concrete - Daslin Solim Juanda Lumban Tobing; Najla Saffanah Putri Saydina; Aizzan Mahmudha; Ikhwan Arief Purnama; Randy Setiawan; Putri Yusella (Buletin Utama Teknik, 2026)
Along with the advancement of time, concrete has undergone many developments in terms of composition and mixture design to achieve optimal and durable performance. Under certain conditions, additives can be incorporated into concrete in specific amounts to enhance its strength. In this study, epoxy resin was added due to its low water absorption and its ability not to hinder paste interaction, thereby improving concrete quality. Fiberglass was also added because of its rigid properties and high tensile strength, which are expected to improve the splitting tensile strength of concrete. This study aims to analyze and compare the compressive strength and splitting tensile strength of normal concrete with concrete mixed with epoxy resin and fiberglass. The research consisted of testing moisture content, specific gravity, sieve analysis of aggregates, slump testing, compressive strength testing, and splitting tensile strength testing of cylindrical concrete specimens at 28 days. The method used in this study was an experimental method with fiberglass variations of 0%, 0.3%, 0.5%, and 0.7%, combined with 1% epoxy resin. The results showed that the compressive strength of concrete mixed with epoxy resin and fiberglass did not increase. At the 0.7% fiberglass variation, a significant decrease in compressive strength was observed, with a result of 11.81 MPa compared to the 0.3% fiberglass variation, which achieved 24.76 MPa. For splitting tensile strength, an increase was observed at the 0.3% fiberglass variation, with a result of 8.49 MPa. Meanwhile, the concrete mixture with 0.7% fiberglass experienced a decrease in splitting tensile strength, with a result of 4.49 MPa.